A Diagnostic Framework to Assess the Capacity of a Government's Financial Management Information System as a Budget Management Tool - Hashim, Ali (World Bank, Washington, DC, 2016)
A government’s capacity to manage its public finances is central to its ability to deliver services. Well-functioning accounting and financial management systems are among the basics that facilitate this, and significant resources and time have been invested for the procurement and implementation of such systems across the world. Implementation is, however, often associated with disappointing results and attribution to higher-level public financial management (PFM) objectives difficult to establish. On the basis of five in-depth project-level evaluations of World Bank investments, this paper proposes a diagnostic framework that can be used to assess the utility of a Financial Management Information System (FMIS) as a budget management tool. The paper develops a total system strength score and weighs various dimensions according to importance. The total system strength score is mapped to corresponding Public Expenditure and Financial Accountability assessment dimensions to assess any correlation between the two, and extensive sensitivity analysis suggests a positive correlation. This is interpreted as an indication that the framework is robust. A preliminary application of the methodology to a sample set of countries finds that in many cases further reforms would be most effective if, at this stage, they pertained to expanding treasury single account and FMIS coverage (and its associated controls) rather than additional technological investments.